PENERAPAN MODEL KOOPERATIF TIPE STUDENT TEAMS ACHIEVMENT DIVISIONS POKOK BAHASAN FUNGSI KELAS VIII SMP - Inderi, Inderi; Yusmin, Edy; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This study aimed to determine the effectiveness of the application of the student teams achievement divisions type of cooperative learning model on function material in the 8th grade SMPN 07 Paloh. The research method was experiment and the form of was pre-experimental design with one shot case study. 28 students of 8th A SMPN 07 Paloh were taken as the research samples. Indicators used to determine the effectiveness of learning using the student teams achievement divisions type of cooperative learning model are : implementation of learning, student’s learning activity, student’s learning outcomes, and student’s responses. Data collection techniques used are documentation techniques, measurement techniques, observation techniques, and indirect communication techniques. The data collection tools are, the implementation of learning observation sheet, the student’s learning activity observation sheet, the student’s learning outcomes test and student’s responses questionnaire. The result of data analysis showed that the implementation of learning are classified as good, the student’s learning activity is active, student’s learning outcomes completeness achieved classically, and students provide a positive responses to learning. The application of the student teams achievement divisions type of cooperative learning model on function material in the 8 th grade SMPN 07 Paloh is effective. Keyword: Application Of Learning, Student Teams Achievement Divisios Type Of Cooperative Model In Learning, Function Material